Sleep habits and height at ages 5 to 11. Issue 1 (January 1990) - Gulliford, M C; Price, C E; Rona, R J; Chinn, S
Abstract : Shorter durations of slow wave sleep and lower growth hormone responses have been reported in children with short stature caused by psychosocial deprivation. We investigated whether lower total sleep duration was associated with shorter stature in a sample of children taking part in the National Study of Health and Growth. Parental responses to a self administered questionnaire were used to estimate usual times for going to sleep at night and usual times for waking in the morning for 5145 children aged 5 to 11 years of age. After adjusting for the effects of other variables known to be associated with height, it was shown that there was a weak negative association between sleep duration and height. It is concluded that variation in sleep duration between children is unlikely to have an important influence on growth.